2020
DOI: 10.3390/jcm9103224
|View full text |Cite
|
Sign up to set email alerts
|

BCG Vaccine Protection against TB Infection among Children Older than 5 Years in Close Contact with an Infectious Adult TB Case

Abstract: The Bacille Calmette–Guérin (BCG) vaccine has been shown to provide considerable protection against miliary or meningeal tuberculosis (TB), but whether it prevents other forms of disease remains controversial. Recent evidence has shown that the BCG vaccine also provides protection against latent TB infection (LTBI). The aim of the current study was to examine whether BCG has a protective role against LTBI among children in close contact with an adult index case in a low TB endemicity setting with the use of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This systematic review and meta-analysis aimed to test if BCG vaccination could protect young people, especially young immigrants, against tuberculosis infection and reinforced recent research on this topic. Previous research done in Indonesia (a high-prevalence country) showed that BCG protection against TB infection was around 48% among examined young children (95% confidence interval 19% to 67%) 8 . Another research done in Greece (a low-prevalence country) represented that BCG protection against TB infection was around 19% among examined young children (95% confidence interval 8% to 29%) 8 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This systematic review and meta-analysis aimed to test if BCG vaccination could protect young people, especially young immigrants, against tuberculosis infection and reinforced recent research on this topic. Previous research done in Indonesia (a high-prevalence country) showed that BCG protection against TB infection was around 48% among examined young children (95% confidence interval 19% to 67%) 8 . Another research done in Greece (a low-prevalence country) represented that BCG protection against TB infection was around 19% among examined young children (95% confidence interval 8% to 29%) 8 .…”
Section: Discussionmentioning
confidence: 95%
“…Previous research done in Indonesia (a high-prevalence country) showed that BCG protection against TB infection was around 48% among examined young children (95% confidence interval 19% to 67%) 8 . Another research done in Greece (a low-prevalence country) represented that BCG protection against TB infection was around 19% among examined young children (95% confidence interval 8% to 29%) 8 . Research results showed that BCG vaccines would help protect adolescents from TB infections.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The current vaccination used to prevent TB is called Mycobacterium bovis bacillus Calmette-Guérin (BCG), and it was first given out in 1921 [35]. The BCG vaccine protects against TB in children between 60 and 80 percent of the time, but it is ineffective against pulmonary TB in adults [36]. Instead of the BCG vaccine, which is only effective in children, the WHO advises pharmacological therapies for TB in adults; their efficacy has also been reported to differ geographically [37].…”
Section: Conventional Treatment Options and Its Limitationsmentioning
confidence: 99%
“…In 1974, the World Health Organization included BCG in its list of vaccines recommended for the Expanded Program on Immunization [ 4 ]. Currently, BCG is administered to more than 100 million neonates per year and provides about 50% protection against clinical TB in children [ 5 ]. However, BCG is a live vaccine, and its administration leads to infection in about 1:10,000 to 1:1,000,000 children [ 6 ].…”
mentioning
confidence: 99%